2019
DOI: 10.1111/ijfs.14136
|View full text |Cite
|
Sign up to set email alerts
|

Superchilled, chilled and frozen storage of Atlantic mackerel (Scomber scombrus) fillets – changes in texture, drip loss, protein solubility and oxidation

Abstract: Summary Changes in quality characteristics in relation to protease activity and protein oxidation in chilled, superchilled and frozen mackerel fillets during storage were studied. The solubility of sarcoplasmic proteins was quite stable in mackerel samples for all storage experiments, whereas the solubility of myofibrillar proteins decreased in both superchilled and frozen samples. A significant correlation (r = 0.983, P < 0.05) between the increased activity of cathepsin B+L in chilled fillets and softening o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 31 publications
0
36
0
1
Order By: Relevance
“…Storage temperature recommended to maintain fish quality and enhance shelf life varies with species, although, −18 °C and −24°C has been suggested for lean and fatty fish species, respectively. Nevertheless, Cropotova, Mozuraityte, Standal, Grovlen, and Rustad (2019) compared the effect of different storage conditions (chilling, superchilling, and frozen storage) and reported that superchilling can reduce the detrimental changes in fish muscles proteins and prevent its structural breakdown compared to frozen storage and chilling. Reduction in protein content as observed in present study can be attributed to autolytic degradation of protein catalyzed by enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Storage temperature recommended to maintain fish quality and enhance shelf life varies with species, although, −18 °C and −24°C has been suggested for lean and fatty fish species, respectively. Nevertheless, Cropotova, Mozuraityte, Standal, Grovlen, and Rustad (2019) compared the effect of different storage conditions (chilling, superchilling, and frozen storage) and reported that superchilling can reduce the detrimental changes in fish muscles proteins and prevent its structural breakdown compared to frozen storage and chilling. Reduction in protein content as observed in present study can be attributed to autolytic degradation of protein catalyzed by enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Superchilling is the process of lowering the temperature of a product just below its initial freezing temperature and the proportion of water frozen is approximately 5-30% preserved within the food product [5][6][7][8]. Superchilling has been used in fish processing to help significantly increase the shelf life and has been successfully applied in the preservation of Atlantic mackerel [9], hairtail [10], olive flounder [11], and seabream [12] as well as other seafood products. Aside from the temperature control, modified atmosphere packaging (MAP) could also inhibit the growth of spoilage microflora on fish [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Superchilling is the process of lowering the temperature of a product just below its initial freezing temperature and the proportion of water frozen is preserved approximately 5-30% within the food product [6][7][8][9]. Superchilling has been used in the fish processing to significantly increase the shelf life and has been successfully applied in preservation of Atlantic mackerel [10], hairtail [11], olive flounder [12], seabream [13], as well as other seafood products.…”
Section: Introductionmentioning
confidence: 99%